Lactic Acid Bacteria from Tempeh and Their Ability to Acidify Soybeans in Tempeh Fermentation - TATI BARUS; GABRIELA GIOVANIA; BIBIANA W LAY (Microbiology Indonesia, 2020)
Tempeh is the most famous traditional fermented food in Indonesia. Tempeh fermentation consists of two stages. In the first stage, the acidification of soybeans used bacteria around 24 hours. Lactic acid bacteria are found in tempeh. Therefore, this study is aimed to investigate the diversity of LAB from tempeh based on 16S rRNA gene sequences and to study their function in tempeh fermentation. In this study, twenty-two LAB isolates were obtained from tempeh. The isolates were closely related to Lactobacillus agilis, Lactobacillus fermentum, Weissella confusa, and Lactobacillus delbrueckii. L. fermentum (13 isolates) were the most abundant in tempeh, followed by L. agilis (7 isolates). It was found LAB important for the acidification of soybeans which the pH of soybean soaking water decreased from pH 7 to pH 4.4-4.9. Key words:Â  diversity, LAB, Lactobacillus,t empeh, Weissella